Lynx Prototoxins: Roles of Endogenous Mammalian Neurotoxin-Like Proteins in Modulating Nicotinic Acetylcholine Receptor Function to Influence Complex Biological Processes - Miwa, Julie M.; Anderson, Kristin R.; Hoffman, Katie M. (Frontiers in Pharmacology, 2019)
The cholinergic system underlies many biological functions, due to the widespread distribution of cholinergic neurons, and the diffuse release of its neurotransmitter, acetylcholine. Several layers of regulation help to refine and control the scope of this excitatory neurotransmitter system. One such regulatory mechanism is imparted through endogenous toxin-like proteins, prototoxins, which largely control the function of nicotinic receptors of the cholinergic system. Prototoxins and neurotoxin share the distinct three finger toxin fold, highly effective as a receptor binding protein, and are expressed in the mammalian brain, immune system, epithelium, etc. Prototoxins and elapid snake neurotoxins appear to be related through gene duplication and divergence from a common ancestral gene. Protein modulators can provide a graded response of the cholinergic system, and within the brain, stabilize neural circuitry through direct interaction with nicotinic receptors. Understanding the roles of each prototoxin (e.g. lynx1, lynx2/lypd1, PSCA, SLURP1, SLURP2, Lypd6, lypd6b, lypdg6e, PATE-M, PATE-B, etc.), their binding specificity and unique expression profile, has the potential to uncover many fascinating cholinergic-dependent mechanisms in the brain. Each family member can provide a spatially restricted level of control over nAChR function based on its expression in the brain. Due to the difficulty in the pharmacological targeting of nicotinic receptors in the brain as a result of widespread expression patterns and similarities in receptor sequences, unique interfaces between prototoxin and nicotinic receptor could provide more specific targeting than nicotinic receptors alone. As such, this family is intriguing from a long-term therapeutic perspective.